LIÇÕES DA EXPERIMENTAÇÃO DO ENSINO MÉDIO INTEGRADO COMO PROJETO DE EMANCIPAÇÃO | Lessons of Integrated High School experimentation as an emancipation project (Trabalho & Educação, 2017)
This article discusses experiences of implementation of Integrated Higher Education in Brazil. By means of a bibliographic and field research. It showed that several subjects, networks and educational units produced orientations and / or implemented actions inspired by the idea of integrated teaching and register difficulties and positivities in this experimentation. It emphasizes that the attempts of integrated teaching reveal more advances when articulated to evident political projects of human emancipation, such as in the studied experience of the Rural Familiar House of Gurupá-Pará. In the conclusion, it is emphasized that from these positive experiences important lessons can be drawn from integrated teaching, which should be understood not only as a pedagogical proposal, but above all as a political banner of the democratic field towards the poor quality of brazilian public education, which reserves only fragments of the literate culture to young people of working class. ___Este artigo aborda as experiências de implementação do Ensino Médio Integrado no Brasil. Por meio de pesquisa bibliográfica e de campo revela que vários sujeitos, redes e unidades de ensino produziram orientações e/ou implementaram ações inspiradas pela ideia de ensino integrado e registra dificuldades e positividades nessa experimentação. Destaca que as tentativas de ensino integrado revelam mais avanços quando articulados a projetos políticos claros de emancipação humana, como na experiência estudada da Casa Familiar Rural de Gurupá-Pará. Na conclusão é enfatizado que dessas experiências positivas podem ser extraídas importantes lições de ensino integrado, que deve ser entendido não apenas como proposta pedagógica, mas, sobretudo, como uma bandeira política do campo democrático, em direção ao enfrentamento da má qualidade da educação pública brasileira, que reserva apenas fragmentos da cultura letrada aos jovens de origem trabalhadora.